2022
DOI: 10.14744/semb.2022.14554
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Thyroid Stimulating Hormone Level and Aggressive Pathological Features of Papillary Thyroid Cancer

Abstract: T hyroid cancer has an increasing incidence due to the increase in diagnostic imaging modalities. Papillary thyroid carcinoma (PTC) is the most common differentiated thyroid cancer (DTC). [1] However, the etiology has not been clarified much, except for reasons such as age, a history of radiation to the neck region, and a previous history of PTC, which predispose to DTC. [2] Thyroid-stimulating hormone (TSH) is the main regulator and growth factor of the thyroid. Since it is the major hormone stimulating thyro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 21 publications
(27 reference statements)
0
5
0
1
Order By: Relevance
“…[ 1 , 2 ] Data from 2 studies by Haymart et al [ 8 , 20 ] demonstrated that gender significantly affects TSH levels between benign and malignant lesions. Although, other studies by Demircioglu et al [ 22 ] and Golbert et al [ 4 ] did not show a gender effect on TSH levels.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…[ 1 , 2 ] Data from 2 studies by Haymart et al [ 8 , 20 ] demonstrated that gender significantly affects TSH levels between benign and malignant lesions. Although, other studies by Demircioglu et al [ 22 ] and Golbert et al [ 4 ] did not show a gender effect on TSH levels.…”
Section: Discussionmentioning
confidence: 81%
“…[ 9 ] Demircioglu et al and Besler et al had similar results. [ 22 , 29 ] Recently, Kim et al [ 30 ] have shown that preoperative TSH levels are a considerable predictive factor for the presence of extrathyroidal spread and lateral LNM in patients with thyroid cancer.…”
Section: Discussionmentioning
confidence: 99%
“…[ 4 ] The most common subtype of thyroid cancers is PTC and increasing of incidence is related with PTC. [ 13 ] The prognosis of PTC, recurrence rate, follow-up of the disease, and the extent of treatment for cure of PTC has been discussed for a long time.…”
Section: Discussionmentioning
confidence: 99%
“… 9 , 10 Some earlier research showed a link that a high level of thyroid-stimulating hormone (TSH) is linked with thyroid various carcinoma. 11 , 12 …”
Section: Introductionmentioning
confidence: 99%